Proyeksi Traffic Jaringan Gigabit Passive Optical Network Pada Cluster Sumbersari Jembrana - Krisna Andika Putra, Gede; Sukadarmika, Gede; Indra ER, Ngurah (Majalah Ilmiah Teknologi Elektro, 2023)
Abstract—This research was conducted to determine the projected growth of subscribers and traffic in the Sumbersari cluster in five years. This study has three stages, namely collecting customer and traffic data, making projections of customer and traffic growth and analyzing projected customer and traffic growth in the Sumbersari cluster. The results of this study are the existing Sumbersari cluster network using a gigabit passive optical network with fiber to the home architecture with cascading passive splitters 1:8 and 1:8. The Sumbersari cluster has a capacity of 512 subscribers (home pass) and 323 existing customers that have been installed (home connected) with a take-up ratio of 63% and the Sumbersari cluster has an average maximum traffic of 454 Mbps with a traffic capacity of 1000 Mbps. The Sumbersari cluster has projected customer growth in 2026 of 605 customers, so expansion is needed to meet the projected customer growth needs. The Sumbersari cluster has a projected traffic growth in 2026 of 805 Mbps, so there is no need for additional traffic capacity. Keywords— Take up ratio, homepass, homeconnected, traffic